Und täglich grüßt das Murmeltier: Die frühe Bildung muss endlich stärker in den Fokus rücken! - C. Katharina Spieß (Wirtschaftsdienst, 2023)
– Given the high benefits of early education, it is particularly noteworthy that new studies of child development during and shortly after the coronavirus pandemic show negative effects on children. This is true for cognitive and non-cognitive skills as well as mental health. Children from low SES families are particularly affected. Although there are fewer studies for preschool children, the few studies that do exist show similar effects; in particular, the closure of daycare centers had a negative impact on children. Last but not least, parental well-being was affected during the pandemic, which will further impact children's development. The article briefly discusses policy responses in light of these findings. Overall, it argues that education policy should place a much greater emphasis on early education and be more targeted,
Keywords: I24; I26; I31; 330; Bildungswesen; Bildungsökonomik; Deutschland